Optimum Currency Area Criteria and Volatility in ASEAN - Tajul Ariffin Masron; Zulkornain Yusop (Asian Academy of Management Journal of Accounting and Finance, 2006)
The goal of regional integration is to promote greater macroeconomic coordination, and reduce the degree of macroeconomic volatility, in particular exchange rate fluctuations. This paper investigates how well optimum currency area (OCA) variables will work in the context of the ASEAN region when the Singapore Dollar, given its relative stability, is used as an anchor currency. The results indicate that OCA variables play an important role in explaining bilateral exchange rate volatility. In addition, exchange rate volatility exerts a negative impact on bilateral trade and gross domestic product (GDP). It is also a source of divergence among ASEAN members.